’Reasonable’ Women Who Kill: Re-Interpreting and Re-defining Women’s Responses to Domestic Violence in England and Wales 1900-1965 - Ballinger, Anette (Outlines. Critical Practice Studies, 2005)
This article makes a contribution to current debates about gender and punishment by providing an historical analysis of the judicial fate of female domestic abuse victims who eventually killed their male abusers between 1900-1965 in England and Wales. Utilising case-studies of women who stood trial for the murder of their abusive partner during this period when murder was still punishable by hanging – I argue that what at first glance appears to be a ‘lenient’ sentence, in fact came at a heavy price for which all women ultimately paid and still pay. That is the maintenance of a gender order which denied women the status of full citizenship. ‘Lenient’ sentencing is shown to be based on stereotypical images of femininity and while it may have appeared to benefit individual women it did nothing to improve the legal situation of battered women generally. These historical case-studies helpwiden our understanding of current debates about gender and punishment by re-interpreting the women’s act of violence. The paper seeks to shift the focus away from provocation, diminished responsibility and irrationality to issues of rationality and agency – without losing sight of the specific circumstances in which the killing took place, and therefore without inviting harsher punishment.